2007
DOI: 10.1007/s10903-007-9075-5
|View full text |Cite
|
Sign up to set email alerts
|

Promoting the Occupational Health of Indigenous Farmworkers

Abstract: In the United States, approximately 78% of agricultural farmworkers are immigrants. In Oregon, a growing number of these farmworkers are indigenous and speak an indigenous language as their primary language. This group of farmworkers suffers from linguistic, cultural and geographic isolation and faces a unique set of challenges yet little has been done to identify their health needs. Using data from focus groups, partners from this community-based participatory research project examined indigenous farmworkers'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
63
1

Year Published

2009
2009
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 23 publications
3
63
1
Order By: Relevance
“…With input from all project partners, 7 we used previously validated survey tools that had been used with farmworkers 5,8,9 to develop a baseline survey written in Spanish. Between April and October 2006, the indigenous community educator partners administered the baseline survey at labor camps, farmworker homes, and community centers.…”
Section: Methodsmentioning
confidence: 99%
“…With input from all project partners, 7 we used previously validated survey tools that had been used with farmworkers 5,8,9 to develop a baseline survey written in Spanish. Between April and October 2006, the indigenous community educator partners administered the baseline survey at labor camps, farmworker homes, and community centers.…”
Section: Methodsmentioning
confidence: 99%
“…Despite the aforementioned risks associated with agricultural work, migrant farmworkers generally lack access to health care services (over two-thirds of all farm workers lack health insurance) (Carr, 2006;Farquhar et al, 2008;Hoerster et al, 2010;McCauley, 2005;McCauley et al, 2006;National Center for Farmworker Health, n.d.b;Sherrill et al, 2005;Zuskin et al, 1997). If a migrant farmworker becomes sick or injured, he or she may face several barriers to accessing health care (Bustamante et al, 2009;Hoerster et al, 2010;Kullgren, 2003;Marshall et al, 2005;McCauley, 2005).…”
Section: Access To Health Care In Oregon For Latino Farmworkersmentioning
confidence: 99%
“…The Latino population (described by the US Census Bureau as "persons of Hispanic or Latino origin") is the largest ethnic minority in the US accounting for nearly 16% of the US population (Denavas-Walt, Proctor, & Smith, 2010;Shah & Carrasquillo, 2006). When compared with other races and/or ethnic groups in the US, Latinos are the most likely to be uninsured with 32% of all Latinos lacking health insurance (Denavas-Walt, Proctor, & Smith, 2010;Farquhar et al, 2008;Hoerster, Beddawi, Peddecord, & Ayala, 2010;Mueller, Patil, & Boilesen, 1998; National Center for Farmworker Health, 2011;Shah & Carrasquillo, 2006). A subset of the Latino population that is particularly vulnerable to health care disparities is undocumented immigrants (Hoerster et al, 2010;Shah & Carrasquillo, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…6 Yoo exposed undergraduate students to Web banner advertisements and found that students who had been exposed to an advertisement for a brand were more likely to choose that brand in a later test than were those not exposed to the advertisement for that brand. 6 To date, only a handful of studies in the United States 3,4,7,8 In an attempt to provide further information on the food and beverage marketing to which children are exposed online, we examined Web sites popular with children to determine whether the sites contained depictions of branded foods and beverages. We also assessed the nutritional value of any marketed products on these Web sites and evaluated their appropriateness for school-age children.…”
Section: About the Authorsmentioning
confidence: 99%
“…This approach puts it within a relatively small group of agricultural health CBPR programs. [5][6][7] Second, the work team included both farmworkers and agricultural employers together, and there was substantial interaction between them. In fact, the work team in New York ultimately selected a health issue that affected workers and farm owners equally, thus strengthening the coalition.…”
mentioning
confidence: 99%